Lateral AlGaN/GaN diode with MIS‐gated hybrid anode for high‐sensitivity zero‐bias microwave detection. Issue 23 (1st November 2015) - Zhou, Qi; Liu, Li; Zhou, Xingye; Zhang, Anbang; Shi, Yuanyuan; Wang, Zeheng; Wang, Yuan Gang; Fang, Yulong; Lv, Yuanjie; Feng, Zhihong; Zhang, Bo
Abstract : A zero‐bias microwave detector using an AlGaN/GaN‐on‐Si lateral diode featuring a recessed metal/Al2 O3 /III‐nitride (MIS) gated hybrid anode (MG‐HAD) is experimentally demonstrated. The forward turn‐on voltage of the MG‐HAD is determined by the threshold‐voltage of the 2DEG channel beneath the recessed MIS‐gate, and thus the nonlinearity of the device at zero bias can be flexibly modulated by gate recessing. The optimal trench depth of the MIS‐gate for zero‐bias detection was designed and experimentally determined to be ∼23 nm, which enables a high‐curvature coefficient of 78 V −1 at zero bias. The first‐order voltage sensitivity, β V, is as high as 7.8 mV/μW. To the best of the authors' knowledge, these values are the highest reported for GaN‐based zero‐bias detectors to date.